Analisis Framing Pemberitaan Tiga Tahun Pemerintahan Joko Widodo dan Jusuf Kalla di Majalah Gatra - Diah Permata Sari (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
This study aims to to see how news magazine weekly phrase framing news related three years of Joko Widodo and Jusuf  Kalla in the viewing angle political and law enforcement to know partiality phrase in long time. Research methodology used is the method research analysis the contents of qualitative. Technique the analysis used is analysis framing model robert entman with four device unit analysis, define the problem, diagnose cause, make moral judgement, treatment recommendation. News who are the objects of research were the reports on the main special edition three years of Jokowi-JK related politics and law enforcement that rises on the 19-25 october 2017 who a total of four news. This research result indicates that magazine phrase in framing news tending to subjective and sided with the government. This could be seen on the narrative of the way of the spread, visual image , the appearance of the institutions to provide assistance to and results of the evaluation various surveys show signs of, and the selection of the source of information that is less in equal proportions between five plus and minus one government s performance evaluation issues account for freedom of expression, SARA, and the consensus of some national .